Trophic plasticity in a common reef‐building coral: Insights from δ13C analysis of essential amino acids. (16th September 2019) - Fox, Michael D.; Elliott Smith, Emma A.; Smith, Jennifer E.; Newsome, Seth D.
Abstract: Reef‐building corals are mixotrophic organisms that can obtain nutrition from endosymbiotic microalgae (autotrophy) and particle capture (heterotrophy). Heterotrophic nutrition is highly beneficial to many corals, particularly in times of stress. Yet, the extent to which different coral species rely on heterotrophic nutrition remains largely unknown because it is challenging to quantify. We developed a quantitative approach to investigate coral nutrition using carbon isotope (δ 13 C) analysis of six essential amino acids (AAESS ) in a common Indo‐Pacific coral ( Pocillopora meandrina ) from the fore reef habitat of Palmyra Atoll. We sampled particulate organic matter (POM) and zooplankton as the dominant heterotrophic food sources in addition to the coral host and endosymbionts. We also measured bulk tissue carbon (δ 13 C) and nitrogen (δ 15 N) isotope values of each sample type. Patterns among δ 13 C values of individual AAESS provided complete separation between the autotrophic (endosymbionts) and heterotrophic nutritional sources. In contrast, bulk tissue δ 13 C and δ 15 N values were highly variable across the putative food sources and among the coral and endosymbiont fractions, preventing accurate estimates of coral nutrition on Palmyra. We used linear discriminant analysis to quantify differences among patterns of AAESS δ 13 C values, or 'fingerprints', of the food resources available to corals. This allowed for the development of a quantitative continuum of coral nutrition that can identify the relative contribution of autotrophic and heterotopic nutrition to individual colonies. Our approach revealed exceptional variation in conspecific colonies at scales of metres to kilometres. On average, 41% of AAESS in P. meandrina on Palmyra are acquired via heterotrophy, but some colonies appear capable of obtaining the majority of AAESS from one source or the other. The use of AAESS δ 13 C fingerprinting analysis offers a significant improvement on the current methods for quantitatively assessing coral trophic ecology. We anticipate that this approach will facilitate studies of coral nutrition in the field, which are essential for comparing coral trophic ecology across taxa and multiple spatial scales. Such information will be critical for understanding the role of heterotrophic nutrition in coral resistance and/or resilience to ongoing environmental change. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.